Concept Analysis and Implementation of “Kampus Merdeka” in Civics Learning for PGMI Study Program Students - Muhammad Shaleh Assingkily; Kharis Sulaiman Hasri; Eyzi Pratiwi; Putri Amanda Fadilla; Tasya Sabrina (Journal of Contemporary Gender and Child Studies, 2023)
This research aims to investigate the implementation of Kampus Merdeka as an innovation in higher education in Indonesia, with a focus on Civic Education (Pendidikan Kewarganegaraan or PKN) learning. The research method used is qualitative with a literature review approach, exploring the concepts and implementation of Kampus Merdeka and its impact on the development of students' skills. The results show that Kampus Merdeka provides autonomy and flexibility to students, stimulates innovation, and creates an adaptive learning environment. The implementation of this program in PKN has successfully made a positive contribution to the demographic bonus through mandatory learning and integrating service learning to enhance student engagement in the community. Despite facing challenges such as efficient academic management and limited resources, Kampus Merdeka Belajar is considered a strategic step in the transformation of higher education. In conclusion, Kampus Merdeka serves as an innovative platform supporting student development, aligning learning with the demands of the times, and reaffirming commitment to the quality of higher education in Indonesia.